Renal embolization for trauma: a narrative review - Peter Lee; Simon Roh (Journal of Trauma and Injury)
Renal injuries commonly occur in association with blunt trauma, especially in the setting of motor vehicle accidents. Contrast-enhanced computed tomography is considered the gold-standard imaging modality to assess patients for renal injuries in the setting of blunt and penetrating trauma, and to help classify injuries based on the American Association for the Surgery of Trauma injury scoring scale. The management of renal trauma has evolved in the past several decades, with a notable shift towards a more conservative, nonoperative approach. Advancements in imaging and interventional radiological techniques have enabled diagnostic angiography with angiographic catheter-directed embolization to become a viable option, making it possible to avoid surgical interventions that pose an increased risk of nephrectomy. This review describes the current management of renal trauma, with an emphasis on renal artery embolization techniques.